Sarcoptic mange of camel in upper Egypt: Prevalence, risk assessment, and control measures (Journal of Advanced Veterinary and Animal Research, 2015)
This study was designed to reveal out  the  prevalence of    Sarcoptic  mite  infestation  and  the  risk  factors associated with occurrence of mange in one-humped camels  (Camulus  dromedarius)  at  smallholder  farms in  Upper  Egypt,  and  to  develop  an  applicable therapeutical  protocol  for  the  Sarcoptic  mange infested  camels.  A  total  of  660  one-humped  camels were  randomly  selected  from  different  villages  of Assiut,  Upper  Egypt.  The  animals  were  undergone clinical  and  parasitological  examinations.  Skin scrapings  revealed  that  Sarcoptes  scabiei  var.  cameli mite  was  present  in  6.06%  (n=40/660)  camels  of  the area.  Statistical  analysis  of  some  ecological parameters  showed  that  there  was  significant relationship  (P